Joint radio resource management in heterogeneous wireless networks - Suleiman, Kamil Hussien (Department of Electrical Engineering, 2023)
The complementary nature of wireless access technologies has resulted in the concept of the integration of overlaid wireless access networks to create a robust and ubiquitous system called heterogeneous wireless networks. In such a system, any mobile user running any application can connect to any of the available access technologies. The envisaged heterogeneous wireless networks will create a more efficient and cost-effective system for service providers and better services to network users. However, the integration of different access technologies is a considerable technological challenge. Designing a good joint radio resource management (JRRM) scheme for a heterogeneous wireless network is part of the integration challenges. The design goal of a JRRM is optimising the trade-off between resource utilisation, quality of service provisioning, fairness, and simplicity of design, amongst others. The diversity of wireless access networks and the resulting complexity of interworking different access networks leave many issues of the JRRM open. The fact that many analytical as well as simulation models of heterogeneous wireless networks are not based on fairly realistic assumptions often affects the practicality of research outputs. In this work, we design JRRM taking into consideration different features of component access technologies of a heterogeneous wireless environment. We also consider different important realistic features of access networks, such as asymmetry of their overlap and the variability of network resources according to traffic conditions. We use the network simulator (ns-2) to validate our design.